(untitled) (Bangladesh Journal of Anatomy, 2011)
Context: Pathological process in the gallbladder occur commonly in association with ageing and includes cholelithiasis, cholecystitis and gallbladder carinoma. Detailed histological knowledge will help surgeon, sonologist and pathologist to adopt appropriate plan for diagnosis and treatment of gallbladder disease. Study type: Descriptive type of study. Place and period of study: Department of Anatomy, Dhaka Medical College, Dhaka from November 2008 to April 2009. Materials: 70 post mortem human gallbladder were collected from unclaimed dead bodies that were under examination in the department of Forensic Medicine of Dhaka Medical College, Dhaka. Method: The samples were divided into three age groups i.e. group A (10-20 years), Group B (21-40 years), group C (41-60 years). Histological study was carried out on relatively 20 fresh samples. Result: The mean thickness of the mucosal layer ranges from 0.403± 0.004 to 0.428± 0.010 mm, fibromuscular layer ranges from 0.933 ± 0.012 to 0.948± 0.003 mm and the serosal layer ranges from 0.397± 0.006 to 0.425± 0.018 mm. Statistically significant positive correlation (p<0.001) was found between age and thickness of different layer of gallbladder. There was no statistically significant sex difference was found in between any age group. Conclusion: There was change in thickness of different layers of gallbladder in relation to age. Key words: Gallbladder; Histology; Thickness. DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8147 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 41-44